Growth Performance of On-Farm Male Fattening Bali Cattle Fed with Fodder Obtained from Dry Land Farming Diversification in West Timor - Maranatha, Grace; Pellokila, Marthen R; Manu, Arnold E; Sobang, Yohanis Umbu L; Nulik, Jacob; Samaba, Fredeicus Dedy (ANIMAL PRODUCTION, 2023)
This study aims to determine the effect of feeding fodder obtained from diversified dry land farming on daily weight gain, chest girth, shoulder height, and body length of male fattening Bali cattle. This study used a double Latin square design (LSD) with 4 treatments, namely T0 = local feed of farmers in Timor (farmer model). T1 = Diversified farm feed (T1 + mulato grass), T2 = T1 + legume Clitoria tarnatea, T3 = T2 + horticulture by-product using 4 periods as replicates. The livestock observed were eight male Bali cattle aged eight months to one year and weighed 97-121 kg (average 108.5 kg). The results showed that the feeding fodder obtained from the diversified farming had a significant effect (P<0.05) on daily body weight gain but not significant (P>0.05) on the linear body size measurements (chest girth, shoulder height, and body length). Considering the economical and convenient features, T2 feed treatment provided a greater contribution of 21.74% compared to control.